PENGEMBANGAN SUMBER BELAJAR BIOLOGI BERBASIS KARTU BERGAMBAR DILENGKAPI MEDIA GAME OBINO (Onet Binomial Nomenclature) PADA MATERI DUNIA TUMBUHAN - Rahmayani Rahmayani (UNM Journal of Biological Education, 2021)
This research is motivated by the existence of problems in the field based on the results of interviews with biology teachers class X MIPA 5 Senior High School that the learning resources used in the biology learning process, especially about the material of plant world, are still conventional and their availability is still very lacking, make students bored. In addition, based on the analysis of the needs students as much as 100 requires learning resources that are more innovative and based technology. The purpose of this research is to develop biological learning resources based on picture cards completely by media game OBINO on valid and practical on plant world. This research is a type of research and development using the ADDIE model and produces learning resources for Flora Angiospermae. The results of expert validator on the learning resources of Flora Angiospermae are very valid based on the percentage of validator assessment, which is 91.80% and are very practical based on the percentage of practitioner assessment (teacher response), namely 92.00% and the percentage of practitioner assessment (student response) 91.08%, so it is feasible used in the learning process.[R1]  Keywords: Game OBINO, Learning Resources, Plant world, Picture Cards.